2000
DOI: 10.1149/1.1393979
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical Formation in H[sub 2]O[sub 2]-Amino Acid Mixtures and Chemical Mechanical Polishing of Copper

Abstract: Chemical mechanical polishing (CMP) has become the key planarization technology in ultralarge scale integration (ULSI) silicon device manufacturing to fabricate sub-quarter-micrometer metal and dielectric lines. [1][2][3][4] In the CMP process, planarization is achieved by polishing a wafer with uneven topography using a colloidal slurry consisting of sub-micrometer sized abrasive particles. The particles are dispersed in an aqueous solution containing various chemicals, which make up the slurry. These chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 13 publications
6
103
0
Order By: Relevance
“…The electrochemical data generated by Brusic and coworkers [16] suggested that H 2 O 2 and glycine promote the formation and removal of a Cu(II) oxide film. Li and coworkers [17] further investigated the formation of the Cu-glycine complex and its effect on the copper film removal rate and static state dissolution rate. It was concluded that the Cu-glycine complex formed during CMP enhanced the decomposition of H 2 O 2 to give hydroxyl radical (*OH).…”
Section: Nitric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical data generated by Brusic and coworkers [16] suggested that H 2 O 2 and glycine promote the formation and removal of a Cu(II) oxide film. Li and coworkers [17] further investigated the formation of the Cu-glycine complex and its effect on the copper film removal rate and static state dissolution rate. It was concluded that the Cu-glycine complex formed during CMP enhanced the decomposition of H 2 O 2 to give hydroxyl radical (*OH).…”
Section: Nitric Acidmentioning
confidence: 99%
“…Although the function of hydrogen peroxide as an oxidizer is well known, the role of glycine in Cu CMP was somewhat less clear. In a study reported by Li and coworkers [17], the main role of glycine was defined as a chelating agent to form a complex with the Cu 2+ ions generated during the polishing process. The complex can catalyze the decomposition of hydrogen peroxide leading to the formation of hydroxyl radicals (*OH).…”
Section: Amino Acidsmentioning
confidence: 99%
“…However, the copper-polish rate with H 2 O 2 -only slurries is low and complexing agents are usually added to improve the dissolution of copper. Among the potential candidates, amino acids 14,15 have been extensively studied. Copper-polish rates increase significantly with addition of glycine to H 2 O 2 -containing slurries, as shown in Table I, due to the formation of soluble copper 2+ -glycine chelate which catalyzes the decomposition of H 2 O 2 to yield *OH radicals.…”
Section: Chemical Componentsmentioning
confidence: 99%
“…Copper-polish rates increase significantly with addition of glycine to H 2 O 2 -containing slurries, as shown in Table I, due to the formation of soluble copper 2+ -glycine chelate which catalyzes the decomposition of H 2 O 2 to yield *OH radicals. 15 However, an inherent problem arising from the enhanced dissolution rate is copper-line corrosion and dishing. As a solution, inhibitors are introduced to prevent etching of the low-lying features without significantly sacrificing the removal rate.…”
Section: Chemical Componentsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is the oxidant most widely used to 'extract' electrons from copper. [1][2][3][4][5][6] The resulting ions easily hydrolyze at neutral and alkaline pH forming insoluble oxide films that hinder the oxidation. The role of complexing agents is to dissolve the oxides and ensure the access of H 2 O 2 molecules to the metal.…”
mentioning
confidence: 99%